2003
DOI: 10.1002/nme.674
|View full text |Cite
|
Sign up to set email alerts
|

DSC solution for flow in a staggered double lid driven cavity

Abstract: SUMMARYA benchmark quality solution is presented for ow in a staggered double lid driven cavity obtained by using the wavelet-based discrete singular convolution (DSC). The proposed wavelet based algorithm combines local methods' exibility and global methods' accuracy, and hence, is a promising approach for achieving the high accuracy solution of the Navier-Stokes equations. Block structured grids with pseudo-overlapping subdomains are employed in the present simulation. A third order RungeKutta scheme is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…Theoretically, the steady state solution, if one exists, should be symmetric with respect to either of the diagonals. However, at higher Reynolds numbers, a steady state solution may not exist as reported by Zhou et al (Zhou et al 2003).…”
Section: Double-driven Cavitymentioning
confidence: 85%
See 2 more Smart Citations
“…Theoretically, the steady state solution, if one exists, should be symmetric with respect to either of the diagonals. However, at higher Reynolds numbers, a steady state solution may not exist as reported by Zhou et al (Zhou et al 2003).…”
Section: Double-driven Cavitymentioning
confidence: 85%
“…Geometry and mesh was chosen. This problem was suggested as a benchmark by Zhou et al (Zhou et al 2003), and it is a diagonally symmetrical enclosure with a longer side of size L and a smaller side of size 0.4L. The top lid is assumed to move at a prescribed positive horizontal velocity and the bottom lid moves with a negative velocity, with a magnitude equal to the velocity of the top lid.…”
Section: Double-driven Cavitymentioning
confidence: 99%
See 1 more Smart Citation
“…The two most representative cases discussed in the literature as demonstrators of algorithms for the numerical solution of the equations of motion in complex geometries are the L-shaped cavity, introduced by Perng & Street (1991) and further studied by Oosterlee et al (1993), and the two-box-cavity proposed by Hinatsu & Ferziger (1991), which is still the subject of intense research (e.g. Zhou et al 2003;Nithiarasu & Liu 2005;Ahusborde & Glockner 2010). One of the investigation's closest related with the present work is the analysis of lid-driven cavity flow in a two-dimensional domain of quarter-circular cross-section by Vynnycky & Kimura (1994), who reported steady flow patterns in Re e [0,1000].…”
Section: Introductionmentioning
confidence: 99%
“…The unified feature of the DSC formalism was discussed and it was demonstrated that computational methods of Galerkin, collocation, global, local and finite difference types can be derived from a single starting point in the framework of the DSC algorithm [24]. The DSC algorithm may be regarded as a local spectral method [25] and it has been used for the treatment of complex boundary conditions in structural analysis [26,27] and applied to computational hydrodynamics [28]. Certain aspects of the convergence of the DSC algorithm have been discussed [25].…”
Section: Introductionmentioning
confidence: 99%